Kajian kepelbagaian dan sistem saraf pusat spesies terpilih ikan air tawar di Malaysia / Mahassan Mamat - Mahassan , Mamat (2017)
Freshwater fish is gaining more attention among researchers, however a complete description of it is still very limited. This study was aimed to investigate the diversity of species and the CNS (brain and spinal cord) of the freshwater fish found in aquatic habitats in Malaysia. Findings obtained were the results of the use of light microscopy to study the morphology of the external body and the CNS while the scanning electron microscope (SEM) to study the topography of the surface of the CNS. The results showed that the freshwater fish demonstrated very high species diversity. A total of 40 families comprising 109 species are commonly found. Each family shows the diversity of different species with the family Cyprinidae having the highest number of species. The external morphology of the freshwater fish showed clear variations of shape whether the part of head, body and tail. Based on the study of brain morphology, the freshwater fish showed external morphology of the brain that varies and very unique. The longitudinal organization of its brain is brief, lobulated and well developed. The structure was divided clearly into three major lobes of the brain, namely telencephalon, optic lobes and cerebellum, and two minor lobes, namely olfactory lobes and inferior lobes. General organizational components of the basis of the brain showed a striking resemblance in all local freshwater fish species. However, external morphology of each lobe of the brain was different in the species and also families. Based on the form, there were two types of brain morphology in freshwater fish. First, Type A in which the formation of the brain component was roundish and uniform, and arranged in rostral-caudal direction. This type was seen in Anabantidae, Channidae, Characidae,